Intelligence, Creativity and Fantasy in Baltasar and Blimunda, by José Saramago - Costa, Maria de La Salette da (2019)
In Baltasar and Blimunda, by José Saramago, intelligence, creativity and fantasy are present in two ways: 1) in the creation of the novel; 2) in the content of the novel. However, according to historiographic metafiction and postmodern historical fiction, Saramago adds to the presence of these faculties and the results they produce in the novel a questioning in the way of Bretch's poem "Questions From a Worker Who Reads", bringing to the forefront the anonymous workers.